Efektivitas Omnibuslaw dalam Pembangunan Investasi (Studi Kasus Perusahaan Tesla.Inc) - Musyfik Fakhri Ali (Jurnal Syntax Transformation, 2021)
The government's ambition to create a friendly business and investment climate in order to increase economic growth and create job opportunities has received a lot of responses from the wider community, and has caused a lot of debate and rejection in the community due to the formation of the Omnibus Law which is aimed at supporting the government's ideals. considered not pro-environment and pro-community and considered only to benefit the elite. The purpose of this study was to determine the effectiveness of the application of the Omnibus Law in building the investment climate in Indonesia. Case study at Tesla.Inc. the research method used is normative juridical. The results show that the Omnibus Law has a tendency to fail in inviting investors to invest their money in Indonesia due to the tendency of countries in the world and world-class companies in this case Tesla.Inc who want environmental improvements so they will not invest money. they are in countries that are not pro-environmental and they also forbid their citizens to invest money in countries that are not pro-environmental whereas if we look at the Omnibus Law, it fulfills these criteria, namely supporting environmental destruction